Botswana : 2010 Article IV Consultation; Staff Report and Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
The economy entered the crisis from a position of considerable strength because of past prudent macroeconomic management. Macroeconomic policies are being appropriately redirected away from short-term demand management toward medium-term considerations. Fiscal policy was strongly countercyclical during the past two years as the government ramped up spending despite a drop in revenues. The framework for managing the government's assets and liabilities needs strengthening to cope with a more challenging fiscal environment. The authorities agreed that their development model would need to change.